A new species of Proneuronema (Neuroptera: Hemerobiidae) from late Eocene Rovno amber - Makarkin, Vladimir N.; Perkovsky, Evgeny E. (Zootaxa, 2020)
Proneuronema sidorchukae sp. nov. (Neuroptera: Hemerobiidae: Drepanepteryginae) is described from the late Eocene Rovno amber, Ukraine. It is most similar to P. minor from Baltic amber, but easily distinguished from it by some crossveins in the third gradate series of the forewing broadly margined with dark brown, the proximal part of the costal space narrower, and proximal subcostal veinlets more oblique. The new species is the smallest known of the genus, with a forewing length of 5.9 mm. Rovno amber hemerobiids show a tendency to decrease in size compared to congeneric or conspecific specimens from Baltic amber. The morphology and terminology of the mesonotum in Hemerobiidae is discussed.